Internet of Things (IoT): Education and Technology. The relationship between education and technology for students with disabilities - Kent, Michael; Ellis, K.; McRae, L. (National Centre for Student Equity in Higher Education, 2018)
In 2016 Curtin University launched its vision for 2030 which frames the development of the campus as a ‘City of Innovation’ as part of its ‘Greater Curtin’ branding. The Internet of Things (IoT) is a key feature of this vision. The IoT enables advanced services through the interconnecting of information and communication technologies. While much of the popular literature about IoT focuses on implications in the home, its benefits to education are just starting to be explored. The creation of smaller, wireless devices that require little power to meet the core functionality – that is, in most cases, to be controlled by a smartphone – provides significant new opportunities for student engagement in the areas of automation and remote controlling of devices. However, many of the IoT uses appearing in education are still in their infancy. As such, there is little information about the benefits, risks and access implications of current IoT solutions for students – this is particularly the case for those students with disabilities. This report details findings of the Curtin University Teaching Innovation funded project Internet of Things (IoT) Education: Implications for Students with Disabilities. This project aimed to provide insight into both the potential risks and benefits of the IoT for tertiary students with disabilities, particularly in the current university climate where this cohort utilise mobile devices as a key resource in their learning. Our key objectives included to: assess the educational benefits of current and emerging IoT products assess the benefits and risks of IoT within a single-interface, app-based interface and whole-of-ecosystem IoT classroom solution by competing providers determine the relevance and implications of IoT as it relates to the educational needs of people with disabilities undertake interviews with currently enrolled students with disabilities to identify the practical needs of this cohort in an educational context provide recommendations and strategic guidance on appropriate IoT solutions with policy recommendations for Curtin University, the tertiary education sector and industry. The report begins with an overview of the history of the IoT and offers a series of definitions of this term. A comprehensive literature review of the IoT follows, addressing both the risks and benefits of the use of IoT in a general as well as in an educational context. This is followed by an in-depth examination of the role of this emerging technology in the lives of students with disability as they move into and through higher education contexts. The report questions the tendency to see technology as an unequivocal benefit to disabled people’s lives and examines the complexities of how technology is integrated into contexts and embodied realities. For example, while the IoT is easily framed as a new and radically nuanced technology that redefines accessibility, an equally decided consideration of the wider significance of the relationships between technology and society, education and disability, access and literacy, also needs circulation. While the IoT can be configured as a champion of and for the social model of disability – where environments can be changed and modified to suit different disabilities – the technology to establish an effective and reflexive IoT infrastructure is not yet at a point where it could be effectively deployed in learning and teaching at the university level. The final section of the report details findings from interviews with currently enrolled Curtin University students with disability. In addition to the risks and benefits outlined in the literature review, these students raised a number of important insights. From the interviews, it can be seen that students with disability at Curtin University state that: The IoT is in a very early stage of development. As such, its possible uses and practicalities are unclear at this stage. They prefer Android devices. Technology must be adaptable. The students we interviewed regularly modify technology to suit their specific needs. They share a widespread willingness to try new technology, and equally a willingness to abandon that technology if it doesn’t provide the support they require. They have different learning styles, for example some are visual, others are aural etc, and therefore require different technologies. Lecturers continue to be unaware of the access needs of students with disability – for example, lecturers are often of the view that if it is digital it is accessible. This was a widespread concern amongst the interviewees. Although the IoT offers great opportunities, it is vital that lecturers retain control of the classroom. They already feel overloaded with information – there is a fear that the IoT could exacerbate this. They hope that the IoT will be able to offer flexible and timely ways to better manage accessing educational materials. These interviews provided insight into what students with disability understand about the IoT, the smart devices they use, and how their learning is facilitated by those devices. However, a more fully-fledged and formed answer to the educational benefits for this cohort can only be speculated on in these early stages of the technology. The report concludes with recommendations about how Curtin University might move forward in creating intelligent design within a campus setting to ensure that students can access cutting-edge education using the IoT. This can take many forms – from the ability to navigate spaces to get to classrooms to being able to download and read online materials in a timely and effective manner – and requires a wide and critical lens. This report recommends, in relation to the deployment of the IoT in an educational setting, that: Curtin University should not immediately deploy IoT technologies, but that careful consideration and planning be undertaken for how this might best be done in the future and what implication this might have. Priority should to be given to incorporating IoT within specific pedagogical issues regarding learning and teaching, with particular consideration being given to the integration of students with disabilities. This is in addition to Curtin’s current focus on integrating IoT technologies primarily in association with facilities management. Any IoT equipment associated with learning should have the ability to provide its output to students via a learning management system or app. This would ensure that students with disabilities can process the data with their preferred assistive technology. Any future implementation of IoT solutions should focus around the use of personal smartphones as the primary IoT interface device for students with disabilities. All IoT-related implementations must also consider privacy, security and interoperability. Any IoT solution must be accompanied by training to ensure that all staff and students are able to use it effectively. The applicability of using a digital assistant as a real-time captioning device warrants further research. A trial of the use of existing technologies and further consultation with industry and students should be undertaken over 2018.